Software architecture : 1 - Oussalah, Mourad (London : ISTE ; Hoboken, HJ : Wiley, 2014)
This book presents software architecture paradigms based on objects, components, services and models. It also discusses the various architectural techniques and methods, the analysis of architectural qualities, models of representation of architectural templates and styles, their formalization, validation and testing, and the engineering approach in which these consistent and autonomous elements can be tackled. --
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed July 16, 2014).
Keywords: Software architecture; Software architecture; Electronic books